The ethics of co-design - Sendra, Pablo (Journal of urban design, 2024)
There is a lack of definition in policy of the term co-design, and yet local authorities and developers are increasingly using it. To avoid that this term becomes meaningless, it is essential to define how to run co-design processes ethically. Building on case studies, professional experience, collaborations with communities, and a Participatory Action Research approach, this paper defines a set of principles on how to run a co-design process ethically and genuinely including communities in decision-making. Departing from the legal Principles for Fair Consultation in England and Wales, the paper expands them and results into ten ethical principles for co-design.